Citra Aktor Politik Pilkada Gubernur dan Wakil Gubernur Provinsi Maluku Utara Tahun 2018 - Burhan Bungin; Nurlaela Syarif; Monika Teguh; Tasya Devi Rossafine (LUGAS Jurnal Komunikasi, 2019)
North Maluku is the youngest province in Indonesia which has begun to carry out democracy through the Election of Regional Heads (Pilkada). One of the largest regional elections in North Maluku is the Governor's Election. Unfortunately the Governor's Election that has been running so far has been colored by various problems. Symbolic violence such as black campaigns by bringing down political opponents using ethnic and primordial issues sprang up. In addition, the ability of figures to build the image of political actors who have power and influence also makes people accept the results of regional elections that are full of disputes. Coupled with the condition of the mass media that have a tendency to take sides because of certain interests, the existence of social construction on the image of political actors is getting stronger. This study wants to see how the image of political actors is constructed. Through the Focused Group Discussion method with the parties involved it was found that social construction of reality had happened through the role of mass media. Although there are social constructions conveyed by the mass media, the community has its own ability to build that image in itself through the power of interaction and communication as well as through the power of other media such as social media.